Fire and Explosion Reduction Analysis for Inherently Safer Design - Elanchelian, Sahriven (Universiti Teknologi PETRONAS, 2016)
Inherent safer design concept design is used to prevent loss prevention and safety management. It works based on the principle of eliminating, preventing and reducing hazards. It does not works based on the traditional method of applying the control measures. Inherent safer design concept can be applied at any stages of design but it will be best to applied at the earlier design stage to save cost and provide a safer result. Lack of software’s and tools for inherent safety concept is the reason for lack usage of the concept. Hence, the objective of this project is to develop fire and explosion index (FEI) program by using Microsoft Visual Basic